In vivo detection of samarium by prompt gamma neutron activation analysis: a comparison between experiment and Monte-Carlo simulation. Issue 12 (22nd October 2015) - Gräfe, James L.; Chettle, David R.; McNeill, Fiona E.
Abstract : Building on previous simulation and experimental work on in vivo detection of gadolinium via PGNAA, we extend this work to incorporate the detection of samarium. Abstract : Building on previous simulation and experimental work on in vivo detection of gadolinium via PGNAA, we extend this work to incorporate the detection of samarium. Samarium, like gadolinium is a rare earth metal with an enormous cross section for neutron capture. The ab initio Monte-Carlo model agrees with experiment to within 2%. There is a wide discrepancy in the gamma emission probabilities for the 149 Sm neutron capture reaction. Decision on the best agreement between simulation and experiment was compounded by a noticed loss in semiconductor detector efficiency due to prolonged neutron damage. We discuss some mechanisms for this loss and reason that the IAEA PGAA database has the most accurate Sm data. We also compare the energy dependence of neutron capture for the non-1/ v absorbers, 149 Sm and 157 Gd, using the 238 Pu/Be source. The initial in vivo detection limit for Sm in a shallow kidney or the human hand bones was found to be 5.5 parts per million (ppm; μg g −1 ). This work has applications to determining the feasibility of neutron activated imaging or for measuring the residual Sm concentration from medical, environmental, occupational, or accidental exposure.